A Variable Magnification Trial Lens Holder - Remole, Arnulf (Canadian Journal of Optometry, 1980)
A variable magnification trial lens holder is described. The unit is designed primarily for producing small order overall and meridional magnification for diagnosing and measuring aniseikonia. However, the unit can be used alternatively as a trial device in low vision.